Challenges – the impact of climate change on the nutritional management of Hungarian orchards - Nagy, Péter Tamás (Acta Agraria Debreceniensis, 2018)
The agricultural sector is increasingly exposed to both environmental and economic risks due to the phenomena of climate change and climate variability. Fruit growth and productivity are adversely affected by nature’s wrath in the form of various abiotic stress factors. Climate change and extreme climatic events are predicted to increase in intensity, frequency, and geographic extent as a consequence of global climate change. It is no doubt that frequency of unexpected climatic events and their growing rate result in an increasing amount of problems for fruit growers globally. Today, climate change impacts are the most serious problems for Hungarian fruit growers as well. It can be stated that the nutrient demand of fruit trees can be supplied only under even worse conditions. Therefore, it is so important to know and apply adaptation and mitigation strategies in horticulture to improve fruit quality and yield. In the last ten years, at the Faculty of Agricultural and Food Sciences and Environmental Management at University of Debrecen expanded studies have been made to prove the importance of groundcover management in horticultural applications. In this mini review paper, is presented, how the university’s researches contributed to the expansion of knowledge of preservation of soil moisture and what advice we can provide for fruit growers to face the challenges of climate change.